Mixed convection analysis in heat transfer enhancement of a nanofluid filled porous enclosure with various wall speed ratios - Nithyadevi, N.; Begum, A. Shamadhani; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Pergamon-Elsevier Science Ltd, 2017)
This study aims to investigate the mixed convection stimulated by a uniformly heated moving lid at the centre of the non-Darcian porous enclosure filled with nanofluid subjected to various wall speed ratios. A nonlinear heating resembling sinusoidal pattern is imposed on the vertical walls, while the horizontal walls are kept adiabatic. The transport equations for fluid and heat are solved using finite volume method with SIMPLE algorithm with a written code. Numerical simulations are carried out for a range of parameters: Richardson number (0.01 <= Ri <= 1), Darcy number (10(-3) <= Da <= 10(-5)), speed ratios (0.5 <= lambda <= 3) and solid volume fraction (0.0 <= phi <= 0.05). The obtained results showed that the mid-moving lid produces an excellent enhancement in heat transfer rate (92.5%) and thereby yields the highest among the conventional moving boundary lids. Further, the heat transfer performance becomes efficient with high Darcy number, maximum speed ratio and increasing nanoparticle volume fraction. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Mixed convection; Porous enclosure; Nanofluid; Non-uniform heating; Speed ratio